2019
DOI: 10.1016/j.jshs.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

An overview of ischemic preconditioning in exercise performance: A systematic review

Abstract: Highlights This systematic review provides a comprehensive review examining the ischemic preconditioning (IPC) literature in sports science over the last 28 years. Studies showed the extent to which IPC can be beneficial to exercise performance. However, not all studies directly observed a positive effect of IPC on exercise performance. The effects of IPC intervention seemed to be more effective in healthy subjects who wished to enhance their performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 76 publications
0
42
0
Order By: Relevance
“…Remote ischemic preconditioning (IPC) is a phenomenon whereby brief cycles of limb ischemia and reperfusion induced by inflating and deflating a blood pressure cuff protect the heart, skeletal muscle, brain, and other tissues against ischemia and other forms of stress (Przyklenk et al, 1993;Gurke et al, 2000), however, the mechanism of this protection is far from being completely understood. The effectiveness of IPC has been demonstrated in randomized clinical trials (Candilio et al, 2013) and in recreational and professional athletes [for reviews see: (Incognito et al, 2016;Horiuchi, 2017;Caru et al, 2019)]. According to several studies, IPC increases the performance during anaerobic and aerobic exercise, and reduces exercise-induced skeletal muscle damage (Franz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote ischemic preconditioning (IPC) is a phenomenon whereby brief cycles of limb ischemia and reperfusion induced by inflating and deflating a blood pressure cuff protect the heart, skeletal muscle, brain, and other tissues against ischemia and other forms of stress (Przyklenk et al, 1993;Gurke et al, 2000), however, the mechanism of this protection is far from being completely understood. The effectiveness of IPC has been demonstrated in randomized clinical trials (Candilio et al, 2013) and in recreational and professional athletes [for reviews see: (Incognito et al, 2016;Horiuchi, 2017;Caru et al, 2019)]. According to several studies, IPC increases the performance during anaerobic and aerobic exercise, and reduces exercise-induced skeletal muscle damage (Franz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, IPC increases the performance during anaerobic and aerobic exercise, and reduces exercise-induced skeletal muscle damage (Franz et al, 2018). Conversely, some studies demonstrated lack of IPC effect on performance (Incognito et al, 2016;Horiuchi, 2017;Caru et al, 2019) as well as some participants are classified as nonresponders for the IPC effect (Franz et al, 2017). Consequently, identifying the molecular mechanism of IPC-induced ischemia and other stress protection might be crucial to the understanding of adaptation to exercise, as well as physiological limits of human performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiac muscle, inducible PGE 2 (via Cox-2) plays an important role in late-phase ischemic preconditioning, which protects the heart from potentially catastrophic outcomes from ischemia [29]. External ischemic preconditioning is considered to be an effective intervention for improving exercise performance [30,31], suggesting that exercise-mediated elevations in PGE 2 may contribute to a desirable adaptation of muscle to exercise stress. Indeed, PGE 2 plays a role in protein synthesis in skeletal muscles following exhaustive eccentric leg exercise in recreationally active human males [32], likely due in part to the stimulatory effect of PGE 2 on the muscle stem-cell function [31], which is impaired in the presence of cyclooxygenase inhibitors [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The application of IPC can increase blood flow in skeletal muscles [17], liver [18], heart [19], and kidneys [20]. This intervention was initially developed to reduce the myocardial damage caused by sustained ischemia [21]; however, IPC affects exercise performance [16,22,23] by improving muscle oxygenation and blood flow to active tissues and organs [24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the hypothesis that IPC may increase heart blood flow and post-reperfusion muscle performance, skeletal muscle research has been initiated by associating IPC with physical exercise [16,[22][23][24]. A few studies have verified the effect of IPC on blood pressure response after exercise, and some studies have verified the effects of IPC applied before cycling tests [22,23] and in running [25], but did not present significant acute reductions in post-exercise blood pressure.…”
Section: Introductionmentioning
confidence: 99%